2021
DOI: 10.1371/journal.pntd.0010062
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and genomic characterisation of the Schistosoma hybrid infecting humans in Europe reveals admixture between Schistosoma haematobium and Schistosoma bovis

Abstract: Schistosomes cause schistosomiasis, the world’s second most important parasitic disease after malaria in terms of public health and social-economic impacts. A peculiar feature of these dioecious parasites is their ability to produce viable and fertile hybrid offspring. Originally only present in the tropics, schistosomiasis is now also endemic in southern Europe. Based on the analysis of two genetic markers the European schistosomes had previously been identified as hybrids between the livestock- and the human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 62 publications
0
28
0
Order By: Relevance
“…The strain was installed in the lab in 1984 after a generous gift of Pr D. Rollinson (British Museum, London). The S. haematobium-bovis hybrid strain was recovered from eggs isolated from a patient infected in the Cavu River, Corsica, France [32]. Since 2014 this strain is maintained in golden hamster as definitive host and Bulinus truncatus (Corsican strain) as intermediate host.…”
Section: Methodsmentioning
confidence: 99%
“…The strain was installed in the lab in 1984 after a generous gift of Pr D. Rollinson (British Museum, London). The S. haematobium-bovis hybrid strain was recovered from eggs isolated from a patient infected in the Cavu River, Corsica, France [32]. Since 2014 this strain is maintained in golden hamster as definitive host and Bulinus truncatus (Corsican strain) as intermediate host.…”
Section: Methodsmentioning
confidence: 99%
“…Three cercariae from each infected snail were individually captured for molecular sexing and each snail was separated into a plastic cup and fed ad libitum. Molecular sexing of S. mansoni and S. bovis cercariae was performed according to [14,28] respectively (see Supplementary Materials for detailed molecular biology protocols [28,29]). The snails were finally separated into four distinct tanks according to sex and species of cercariae.…”
Section: Experimental Protocol 231 Snail Infection and Obtention Of U...mentioning
confidence: 99%
“…These experimental studies have evidenced either random mating or a preponderance of homo-specific pairing according to the phylogenetic distance of the interacting species [13]. When closely related species interact such as S. haematobium × S. bovis [14], S. bovis × S. curassoni [15], S. haematobium × S. intercalatum [16] or S. intercalatum × S. guineensis [17] the pairing is random. All these latter species are included in the same monophyletic S. haematobium group [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Boissier et al reported an outbreak of urogenital schistosomiasis in Europe, in Corsica Island (France), produced by parasites imported from Senegal, and alerted the potential risk of schistosomiasis outbreaks in other European areas [7]. European schistosomes had previously been identified as hybrids between the livestock-and the human-infective species Schistosoma bovis and Schistosoma haematobium, respectively [8,9]. Recently, after an in-depth clinical and epidemiological study of several cases, evidence of autochthonous transmission of urogenital schistosomiasis in Almería (Spain) was demonstrated [10], and new cases of acute schistosomiasis have been reported in people from Antwerp, Belgium after staying in South Africa [11].…”
Section: Introductionmentioning
confidence: 99%